The Quarries of Meroe, Sudan- Part 2 - Catalogue - Thilo Rehren; Brigitte Cech; Abdelrahman Ali Mohamed (Hamad Bin Khalifa University Press, 2021)
"Part 2 is a detailed catalogue of all 92 quarries recorded in the course of the project. All articles have extensive Arabic summaries. Video This two-part set is accompanied by five short educational and illustrative slideshows in English and Arabic about the authors’ work on the sandstone quarries around Meroe. The highlight is a 5-minute aerial and underground ‘fly-through’ video presenting quarry Q41, the largest and most impressive of the gallery quarries in the study area, available in 2D or 3D. All videos are available here: https://www.youtube.com/playlist?list=PL7-ic31cMSbvWosaClqx-qHJYtYWraVgB Acknowledgment This publication and the associated videos were made possible by NPRP grant 5-879-6-025 from the Qatar National Research Fund (a member of Qatar Foundation). The statements made herein are solely the responsibility of the author(s)."